THE ROLE OF A SPORT IN A HEALTHY LIFESTYLE - Asatullayev Rustam Bakhtiyorovich,; Sirojboyev Shahzod Vohidovich, (TADQIQOTLAR, 2026)
Abstract:  This  article  explores  the  significant  role  of  sports  in  promoting  a healthy lifestyle. It discusses how regular participation in sports contributes to physical fitness, mental well-being, and social interaction. The article highlights the various health benefits associated with engaging in sports, including improved cardiovascular health, enhanced muscle strength, and better flexibility. Additionally, it emphasizes the positive impact of sports on mental health, such as reduced stress and anxiety levels, improved  mood,  and  increased  self-esteem.  The  social  aspect  of  sports  is  also examined,  illustrating  how  team  participation  fosters  community,  teamwork,  and communication skills. Overall, the article advocates for the incorporation of sports into daily routines as a vital component of holistic health.